2011
DOI: 10.1007/s13225-011-0092-2
|View full text |Cite
|
Sign up to set email alerts
|

New species of Chalara occupying coniferous needles

Abstract: Chalara is a genus of anamorphic fungi with typical phialidic conidiogenous cells. Species of Chalara live mostly as litter saprotrophs, many of them on coniferous litter. In this study, the morphology and DNA sequences (ITS rDNA, 28S rDNA and EF-1α) of strains of various species of Chalara isolated from coniferous litter needles were compared with those of strains from public collections. The majority of the isolates belonged to the C. longipes. Other strains represent C. piceae-abietis, C. microspora, Infund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…The transition from saprotrophy to endophytism, or vice‐versa, is also described in fungi colonizing the aerial parts of plants (Fig. b), with a striking convergence in ascomycetous taxa that are both litter decayers and endophytes (Selosse et al ., ; Koukol, ). Recurrent transitions from saprotrophy to endophytism may explain the dominance of facultative endophytes in roots, which also behave as soil saprotrophs, e.g.…”
Section: Evolutionary Trajectories and Species Lost In Translationmentioning
confidence: 97%
See 1 more Smart Citation
“…The transition from saprotrophy to endophytism, or vice‐versa, is also described in fungi colonizing the aerial parts of plants (Fig. b), with a striking convergence in ascomycetous taxa that are both litter decayers and endophytes (Selosse et al ., ; Koukol, ). Recurrent transitions from saprotrophy to endophytism may explain the dominance of facultative endophytes in roots, which also behave as soil saprotrophs, e.g.…”
Section: Evolutionary Trajectories and Species Lost In Translationmentioning
confidence: 97%
“…Mycena in orchids (Selosse et al ., ) or Ericaceae (Grelet et al ., ), or they can be common endophytes, such as Xylariales (Davis et al ., ) or Chalara spp. (Koukol, ). Recently, after inoculating 201 saprotrophic species on coniferous seedlings, Smith et al .…”
Section: Do Fungal Ecological Niches Reflect More Than Mycologist's Smentioning
confidence: 99%
“…Previous studies in the area that focused on soil microfungi indicated a greater diversity of fungi compared to other mountain or lowland sites (Nov akov a and Bla zkov a, 2000). Recently, endophytic fungi from the needles of windfallen trees were surveyed, and several new species were described among the isolated strains (Koukol and Kol a rov a, 2010;Koukol, 2011;Koukol et al, 2012). From a historical point of view, the forests in the study area originated through natural regeneration after several disturbances at the end of the 19th century and, except for minor interventions at the beginning of their growth, there has been no forest management (Svoboda, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Infundichalara microchona (anamorph: Chalara microchona W. Gams) is known from decayed and healthy‐looking bark and wood of P . sylvestris, coniferous needles and a basidioma of the Polyporales (Gams & Holubová‐Jechová, ; Koukol, ; Réblová, Gams, & Štěpánek, ). However, it is also known from decayed grass (Koukol, ), and Tyub et al.…”
Section: Discussionmentioning
confidence: 99%